DESCRIPTIVE GEOMETRY: CENTRAL AND PARALLEL PROJECTIONS AND THEIR GEOMETRIC AND MATHEMATICAL PROPERTIES - Yuldashev Solmonjon Iqboljon ugli (Bright Mind Publishing, 2025)
This article provides a comprehensive scientific analysis of the geometric and mathematical foundations and characteristics of central and parallel projections used in descriptive geometry. The scientific significance of projections in the accurate and realistic representation of spatial objects, their wide application in technical fields, and their comparative features are thoroughly explored. The historical development of descriptive geometry, the basic principles of projection theory, and their practical application are also examined in detail.
Keywords: Descriptive geometry, central projection, parallel projection, perspective distortion, spatial perception, Monge method.